Fundamentals of human resource management - Noe, Raymond A. (McGraw-Hill/Irwin, 2007)
Fundamentals of Human Resource Management, by Noe, Hollenbeck, Gerhart and Wright is specifically written to provide a complete introduction to human resource management for the general business manager. This book is the most engaging, focused and applied HRM text on the market